Acute volvulus of the stomach associated with diverticulum of the second portion of the duodenum - Porras, Yamandú; Méndez, Hugo; Criado, F (Cirugía del Uruguay, 1973)
In one case of primitive stomach volvulus associated to a giant diverticulum in 2nd. duodenum, treatment consisted of gastroenterostomy and vagotomy. Evolution was good,